2014
DOI: 10.1002/qj.2334
|View full text |Cite
|
Sign up to set email alerts
|

The response of the Pacific storm track and atmospheric circulation to Kuroshio Extension variability

Abstract: An index of the Kuroshio Extension front strength is produced using a maximum covariance analysis between sea-surface temperature (SST) and sea-surface height (SSH) gradient observations, and composites of the atmospheric state are presented during its positive and negative phases using reanalysis data (1992-2011).It is found that when the Kuroshio Extension is less (more) meandering, with a stronger (weaker) SST front, the atmospheric heat transport by transient eddies is increased in the western (eastern) Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
101
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(113 citation statements)
references
References 65 publications
(68 reference statements)
10
101
2
Order By: Relevance
“…In addition, it was based on temperature profiles that may be too shallow to accurately define the KE path. O'Reilly and Czaja (2015) found that, during the 1992-2010 period, the transient eddy heat transport in winter and spring has a dipolar structure with an increase in the western North Pacific and a decrease in the east when the KE is shifted north and the SST front is stronger, unlike in the present analysis. They used (unlagged) composites based on an index derived from a maximum covariance analysis between SST and SSH gradients during 2002-10.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…In addition, it was based on temperature profiles that may be too shallow to accurately define the KE path. O'Reilly and Czaja (2015) found that, during the 1992-2010 period, the transient eddy heat transport in winter and spring has a dipolar structure with an increase in the western North Pacific and a decrease in the east when the KE is shifted north and the SST front is stronger, unlike in the present analysis. They used (unlagged) composites based on an index derived from a maximum covariance analysis between SST and SSH gradients during 2002-10.…”
Section: Discussioncontrasting
confidence: 78%
“…In this period, their index is very similar to Qiu et al's (2014) index, and we verified that the two indices lead to similar regression patterns in SLP, geopotential, Eady growth rate, and eddy heat transport, albeit different from those discussed here, presumably because the sample is too short to emphasize the decadal KE changes that dominate the response in the present paper. However, the KE indices differ considerably during 1992-2001 when O'Reilly and Czaja's (2015) index was extended by SSH projection, with much larger decadal changes in Qiu et al's (2014) index. Whether the differences in the two analyses are primarily due to the differences in the KE indices or their dominant time scale, or nonstationarity in the atmosphere, remains to be established.…”
Section: Discussionmentioning
confidence: 95%
“…The remote atmospheric response to oceanic fronts and eddies, in comparison to the local response, is generally more difficult to identify using direct observations (Frankignoul et al 2011;O'Reilly and Czaja 2015); hence, most existing studies are based on high-resolution model experiments. A particularly useful experimental strategy for this type of study is a set of twin atmospheric model simulations, one of which is forced by observed SSTs and the other by spatially smoothed SSTs (Xie et al 2002;Minobe et al 2008;Kuwano-Yoshida et al 2010;Small et al 2014b;Piazza et al 2016;X.…”
Section: The Global Hydrological Cyclementioning
confidence: 99%
“…Ma et al 2015X. Ma et al , 2017O'Reilly et al 2017), storm-track strength (Small et al 2014b), and remote rainfall response along the U.S. West Coast to Kuroshio eddies (X. Ma et al , 2017; Kuwano-Yoshida and Minobe 2017).…”
Section: The Global Hydrological Cyclementioning
confidence: 99%
“…The relationship between the storm track and sea surface temperature (SST) fronts associated with western boundary ocean currents, such as the Kuroshio, the Kuroshio Extension, the Oyashio, and the subpolar front in the northwestern Pacific (NWP) as well as the Gulf Stream in the northwestern Atlantic, has been investigated by analyzing observations, reanalysis data, and sensitivity experiments using global and regional atmospheric models in both ideal and realistic situations (Nakamura et al 2004;Minobe et al 2008;Taguchi et al 2009;Sampe et al 2010;Kuwano-Yoshida et al 2010b;Frankignoul et al 2011;Booth et al 2012;Ogawa et al 2012;Taguchi et al 2012;Iizuka et al 2013;KuwanoYoshida et al 2013;Small et al 2014;Smirnov et al 2015;O'Reilly and Czaja 2015;O'Reilly et al 2016;Ma et al 2015;Parfitt et al 2016). Nakamura et al (2004) summarized the relationship among storm tracks, jet streams, and midlatitude oceanic fronts based on observations and reanalyses.…”
Section: Introductionmentioning
confidence: 99%